PENGARUH KECERDASAN INTELEKTUAL, EMOSIONAL, DAN SPIRITUAL (ESQ) DAN LOKUS PENGENDALIAN (LOCUS OF CONTROL) TERHADAP PENERIMAAN PERILAKU DISFUNGSIONAL AUDIT (STUDI PADA BADAN PEMERIKSA KEUANGAN PERWAKILAN SULAWESI TENGGARA) - Dalli, Nasrullah; Asni, Nur; Arba Suaib, Dwi Febrian (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
ABSTRACT The purpose of this study was to determine the effect of Intellectual, Emotional, and Spiritual Quotient (ESQ) and Locus of Control on acceptance of audit dysfunctional behavior by the respondent of the Auditor/Investigator who worked at Badan Pemeriksa Keuangan, Province of South East Sulawesi. Theories related to this research are the theory ESQ, locus of control and Audit Dysfunctional Behavior. The number of samples was determined that as many as 20 respondents using census method. Data taken from the questionnaire was distributed to all respondents and analyzed using descriptive and multiple regression analyss. The results showed 1) ESQ showed significant negative effect on acceptance of audit dysfunctional behavior, 2) Locus of Control showed insignificant positive effect on acceptance of audit dysfunctional behavior, 3) ESQ gave dominant effect on acceptance of audit dysfunctional behavior. Keywords: Intelligence, emotional, and spiritual quotient, locus of control, and audit dysfunctional behavior